Clusterin protects against HFpEF by inhibiting UCHL1-mediated NLRP3 deubiquitylation and inflammasome activation - Yu, Jiangling; Kang, Xiaoxu; Chang, Rui; Zhang, Cheng; Yang, Song; Chen, Lang; Wang, Xinbo; Hu, Bing; Wang, Zixuan; Gong, Lili; Liu, Lihong (Frontiers in Pharmacology, 2026)
BackgroundHeart failure with preserved ejection fraction (HFpEF) poses a serious threat to human health, but effective treatment strategies remain limited. Clusterin (CLU) is a multifunctional glycoprotein implicated in inflammation and tissue remodeling, but its role in HFpEF pathogenesis is not fully understood.MethodsThe effects of CLU in a murine HFpEF model were investigated by adeno-associated virus (AAV)-mediated overexpression and liver-specific knockout approaches. Cardiac function in mice was evaluated by echocardiography, and myocardial inflammation and fibrosis were assessed using Masson’s trichrome staining, real-time qPCR, and Western blot analysis. Protein interactions were identified by immunoprecipitation–mass spectrometry (IP-MS).ResultsAAV-mediated CLU overexpression significantly improved diastolic function and reduced myocardial inflammation and fibrosis in HFpEF mice, whereas liver-specific CLU knockout aggravated disease progression. In vitro, CLU overexpression attenuated inflammatory responses and collagen production in injured cardiomyocytes. Mechanistically, CLU was found to interact with the deubiquitinase UCHL1. CLU overexpression reduced UCHL1 expression, thereby enhancing ubiquitination and degradation of NLRP3, leading to suppression of inflammasome activation and inflammation. Furthermore, treatment with a synthetic CLU-derived peptide markedly alleviated cardiac fibrosis and inflammation in HFpEF mice.ConclusionThis study reveals a novel regulatory mechanism through which CLU alleviates HFpEF by modulating the UCHL1–NLRP3 signaling axis. The findings provide new insight into the anti-inflammatory and anti-fibrotic roles of CLU and suggest that CLU and its derived peptide hold translational potential as therapeutic candidates for HFpEF.